Breast Cancer Incidence Trends and Projections in Northeastern Thailand - Virani, Shama (J Epidemiol, 2018)
BACKGROUND: The northeast has the lowest incidence of breast cancer of all regions in Thailand, although national rates are increasing. The heterogeneity in subnational trends necessitates a comprehensive evaluation of breast cancer incidence trends and projections to provide evidence for future region-specific strategies that may be employed to attenuate this growing burden. METHODS: Joinpoint regression and age-period-cohort modeling were used to describe trends from 1988–2012. Data was projected from three separate models to provide a range of estimates of incidence to the year 2030 by age group. RESULTS: Age-standardized rates (ASRs) increased significantly for all women from 1995–2012 by 4.5% per year. Rates for women below age 50 increased by 5.1% per year, while women age 50 years and older increased by 6% per year from 1988–2012. Projected rates show that women age 50 years and older have the largest projected increase in ASRs by 2030 compared to younger women and all women combined. CONCLUSIONS: Breast cancer trends in Khon Kaen are presently lower than other regions but are expected to increase and become comparable to other regions by 2030, particularly for women ages 50 years and older.